Quality assessment of wine from purple rice (Oryza sativa var. tapul) - Cervantes, Carmela Mae Masnaño
Production of wine using purple glutinous rice, tapul (Oryza sativa var. tapul) as the main substrate was conducted in a factorial experiment in RCBD.